2020
DOI: 10.1093/iob/obaa044
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Derived Monomorphism From Sexual Dimorphism: A Case Study on Salamanders

Abstract: While sexual dimorphism has long received special attention from biologists, derived monomorphism, the condition in which both males and females express similar derived features, has been less well studied. Historically, the appearance of “male-like” features in females has been explained by the genetic correlation between the sexes. Recent work emphasizes the importance of studying the independent selective forces on both females and males to understand sexual dimorphism. Sexual dimorphism and derived monomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…We found preliminary, but inconclusive, evidence for differences in head size and shape that were consistent with our hypothesis that adult males in breeding condition would exhibit enlarged jaw musculature. In particular, our linear model suggests that large P. ruber with cloacal papillae have disproportionately wide heads, similar to patterns described in some Aneides (Staub 2021). Although the results of our analysis of head shape were not statistically significant, they were directionally consistent with our hypothesis, suggesting that specimens with cloacal papillae may have more pointed snouts and wider jaws.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found preliminary, but inconclusive, evidence for differences in head size and shape that were consistent with our hypothesis that adult males in breeding condition would exhibit enlarged jaw musculature. In particular, our linear model suggests that large P. ruber with cloacal papillae have disproportionately wide heads, similar to patterns described in some Aneides (Staub 2021). Although the results of our analysis of head shape were not statistically significant, they were directionally consistent with our hypothesis, suggesting that specimens with cloacal papillae may have more pointed snouts and wider jaws.…”
Section: Discussionsupporting
confidence: 84%
“…This musculature leads to gross morphological differences in head shape and size that are quantifiable without dissection. Plethodontine plethodontid salamanders in the genus Aneides have a superficially similar head morphology (Wake 1963), although the genus exhibits a variable degree of sexual dimorphism across species (Staub 2021). Furthermore, their head dimorphism is apparently associated with more general agonistic behavior rather than strictly with mate-guarding (Staub 1993).…”
Section: T a B L E O F C O N T E N T S F E A T U R E A R T I C L E Smentioning
confidence: 99%
“…For example, Aneides salamanders vary in their degrees of sexual dimorphism (i.e., jaw muscle size and tooth count) and the extent to which they display aggressive behaviors ( Wake 1963 ; Wake et al. 1983 , Staub 1993 , 2021 ). Comparing the tooth function of male and female salamanders may help to better explain the evolution of the novel dentitions found in Aneides salamanders.…”
Section: Resultsmentioning
confidence: 99%
“…Monomorphism is assumed to be the ancestral state, where there is no obvious signature of selection differentiating the sexes. However sexual monomorphism, can also be a derived condition, evolving from sexual dimorphism (Staub, 2020). Results obtained by Owens and Hartley (1998) suggested that size dimorphism is associated with intrasexual competition described by the mating system, meanwhile plumage colour dimorphism is linked to the frequency of extrabond paternity.…”
Section: Discussionmentioning
confidence: 99%